Improving the Skills of Siamese Orange (Citrus nobilis Lour) Farmers in Belantih Village, Bangli, to Prevent Fruit Loss through Organic Cultivation Technology: Improving the Skills of Orange Farmers to Prevent Fruit Loss through Organic Cultivation Technology - Ni Komang Alit, Astiari; Sulistiawati, Ni Putu Anom; Suaria, I Nengah; Andriani, Anak Agung Sagung Putri Risa; Singapurwa, Ni Made Ayu Suardani; Sutapa, I Gede (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Action Research Program for Regional Leading Product Development was conducted in Belantih Village, Bangli. The purpose of this activity is to improve the skills of citrus farmers in Belantih Village, Bangli, in an effort to prevent fruit loss through organic cultivation technology. Participants are administrators and members of the Dharma Kriya farmer group. Implementation of activities using a learning by doing approach. The method of implementing the activity is through counseling and mentoring as well as technology transfer to prevent flower and fruit loss by applying techniques for pruning twigs, water shoots and unproductive branches as well as administering NPK Guano fertilizer at a dose of 500 g/tree, and spraying Agrodyke fertilizer to all parts of the plant at a dose of 500 g/tree. 40 g/l of water. The results of the counseling and mentoring showed that through the implementation of the learning by doing method, they stated that they could easily understand and understand how to do prevention technology so that flowers and fruit do not fall off easily. Based on the results of the tabulation of the questionnaire given, it was found that 92.00% of the 25 respondents stated that they were very satisfied and those who expressed satisfaction were 8.00% with the PPPUD service activities carried out, which means that there were no respondents who expressed dissatisfaction or dissatisfaction. 96.00% of respondents stated that they were very interested in practicing flower and fruit loss prevention technology in their own gardens and the remaining 4.00% said they were interested. This means that 100% of the participants are interested in implementing it in their own gardens.